PSO Supported Ensemble Algorithm for Bad Data Detection Against Intelligent Hacking Algorithm - Yavuz, Levent; Soran, Ahmet; Onen, Ahmet; Muyeen, SM (Frontiers in Energy Research, 2021)
Power system cybersecurity have recently become important due to cyber-attacks. Due to Advanced computer science and machine learning (ML) applications have being used by malicious attackers; cybersecurity is more crucial to create sustainable, reliable, efficient and well-protected cyber-systems. Considering the fact that it is required for power system operators to pay more attention to develop sophisticated detection mechanism. In this study, a novel machine learning based detection algorithm that combines five most popular ML algorithms with Particle Swarm Optimizer (PSO) is developed and tested by using intelligent hacking algorithm that is specially developed to measure of effectives of this study. The hacking algorithm provides three different types of injections: random, continuous random and slowly injections by adaptive manner, so that detection would be harder. Results shows that recall values with proposed algorithm for each different type of attacks have been increased.